WEBSITE E-COMMERCE KERAJINAN KAIN KHAS PALEMBANG UNTUK MENINGKATKAN PENJUALAN - Sa’uda, Siti; Yudiastuti, Helda (JURNAL ILMIAH MATRIK, 2015)
Abstract: This research was carried out on an industrial fabric crafts typical Palembang implementing a system of information technology solutions for marketing by utilizing e-commerce in 16 Ilir market new shopping complex ilir Barat Permai. During this marketing system that they do still conventionally by selling directly to customers who come into their stores.The method used in the development of this software is theWaterfall method Software, This method is suitable for use in this study because this study used CMS Prestashop since waterfall has several stages of coherent. The goal of this research is to produce an e-commerce website cloth merchant group in Palembang typical shopping complex Ilir Barat Permai in an effort to improve marketing and sales. e-commerce system is easier for the user to access information about the product typical Palembang cloth, So that e-commerce is made can be used as an online marketing network development. Keywords : Crafts, fabrics, Prestashop, E-commerce, Waterfall, CMS